Decision Support System Pada Pengirimaan Logistik Menggunakan Metode G-VRPTW - Iswardani, Kurnia; Marzuki, Imam; Haryono, H (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Air pollution gets worse every year; one of the contributing factors to the worsening of air pollution is the increasingly busy delivery of goods between regions and within regions. PT X is a distributor that delivers goods in the form of flour products. Every day. There are 40 consumers in several areas and not close to each other. The vehicles used are several trucks. The problem faced is the high cost of penalties because they often experience delays in the delivery, and the use of fuel is quite high, automatically it will be directly proportional to the air pollution produced. This is one of the cases of the Green Vehicle Routing Problem Time Windows (GVRPTW). These problems include NP-Hard, which means that it takes a lot of computational effort to find the best solution. One method that can be used for this problem is the Ant colony Optimization (ACO) method. The output of this algorithm is the fuel costs and the route that is passed.